ANALISIS KOMPARATIF TINGKAT PENGANGGURAN TERBUKA (TPT) WILAYAH PERKOTAAN PROVINSI SULAWESI UTARA - Yoan Purnamasari Makapuase Bahalau; Zerah Elisa Derek; Marthin Thomas Mumbunan (JURNAL ILMIAH EDUNOMIKA, 2026)
The Open Unemployment Rate (OUR) in urban areas is an important indicator for assessing labor market dynamics and regional economic resilience, particularly in the post–COVID-19 period. This study aims to analyze the level and trends of the Open Unemployment Rate, compare unemployment differences across cities, and examine the factors influencing variations in urban unemployment in North Sulawesi Province. The study employs a quantitative descriptive–comparative approach using official secondary data from Statistics Indonesia (BPS) for the 2020–2024 period, covering the cities of Manado, Bitung, Tomohon, and Kotamobagu. The analytical methods include trend analysis and interregional comparison. The results indicate that unemployment rates in all cities have generally declined alongside economic recovery, although Manado consistently records the highest unemployment rate. Variations in unemployment across cities are influenced by differences in economic structure, dependence on dominant sectors, and labor force characteristics. These findings underscore the importance of locally tailored labor market policies through workforce skill enhancement, economic diversification, and the development of urban priority sectors. Keywords : Open Unemployment Rate; Urban Labor Market; Comparative Analysis; Economic Structure; North Sulawesi